Magneto-Optical Kerr Effect Measurement of Magnetic Thin Films on Self-Assembled Nanospheres - Flores, Brian L.
We are exploring how the topography of substrate surface alters the magnetic property of ferromagnetic monolayer system. Ferromagnetic monolayer has presented an interesting magnetic switching behavior originating from its dependence of the substrate's topography. Using nanospheres we modified the topography of substrate: 880 nm polystyrene nanospheres were uniformly self-assembled on silicon substrate and magnetic materials were deposited on them. Magnetic hysteresis measurements were made with a homemade Magneto Optical Kerr Effect (MOKE) system using a HeNe laser with maximum magnetic field of 1300 Oe. It is observed that nanosphere topography has made a considerable change in switching behavior of thin films compared to the films grown directly onto silicon substrate.